If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Log(10x + 13) = 3 Reorder the terms: goL(13 + 10x) = 3 (13 * goL + 10x * goL) = 3 (13goL + 10goxL) = 3 Solving 13goL + 10goxL = 3 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Reorder the terms: -3 + 13goL + 10goxL = 3 + -3 Combine like terms: 3 + -3 = 0 -3 + 13goL + 10goxL = 0 The solution to this equation could not be determined.
| -14D-6=-3(D+2)-11D | | 2m^2=13m-20 | | X(3-2x)=2x(x-3)+6 | | 2j+2j=16 | | -9h+2h+2h=5 | | 5n^2+8n-85=0 | | -15g+2g+3g+-7g+5g=-12 | | 9-6x=-3 | | 5y-2x= | | 13j+2j-15j+2j=6 | | 8x+(-5)=59 | | 14z+4z-2z-6z-2z=16 | | 3(N+7)=3-3(N-8) | | 3t-3t+t=18 | | 5T=(T+1900)-1500+T+1900 | | 10z+z-2z=9 | | 14g-7g-3g=20 | | 18p-9p=9 | | 6*6-4y=-24 | | 4b+3b=14 | | 2.5c=17 | | z^2+7z-10=0 | | -3y+7=-4y+4 | | 6x+17=2x+5 | | 4(x-2)+8=120 | | 64=x-0.23x | | 8x=9+6(2x+4) | | -6-(3z-2)=5z | | 10y-y=2y+3 | | -19-x+5=6 | | 6x+3=8-21 | | d^2+3d-7=0 |